Intensity of end‐of‐life care for patients with myelodysplastic syndromes: Findings from a large national database. Issue 8 (23rd February 2016) - Fletcher, Sean A.; Cronin, Angel M.; Zeidan, Amer M.; Odejide, Oreofe O.; Gore, Steven D.; Davidoff, Amy J.; Steensma, David P.; Abel, Gregory A.
Abstract : BACKGROUND: As the population ages, the prevalence of myelodysplastic syndromes (MDS) will increase, and many patients with MDS will require end‐of‐life (EOL) care. Little is known about the intensity of EOL care received by patients with these malignancies. METHODS: Using the Surveillance, Epidemiology, and End Results–Medicare database and standard EOL quality measures, we assessed the prevalence and predictors of intensive care unit (ICU) admission in the last 30 days of life, chemotherapy in the last 14 days of life, and hospice enrollment among MDS patients who were 65 years old or older and died between 2006 and 2011. RESULTS: Of 6, 955 patients, 28% were admitted to the ICU and 7% received chemotherapy near the EOL, while 49% enrolled in hospice. In multivariable models, patients dependent on red blood cell or platelet transfusions at the EOL were less likely to enroll in hospice (odds ratio [OR], 0.69; 95% confidence interval [CI], 0.61‐0.78). Nonwhite patients were less likely to enroll in hospice (OR, 0.77; 95% CI, 0.67‐0.89) and more likely to be admitted to the ICU near the EOL (OR, 1.19; 95% CI, 1.03‐1.38). Finally, the prevalence of hospice enrollment increased in later years ( P < .001). CONCLUSIONS: The intensity of EOL care for patients with MDS varies but is potentially suboptimal with respect to the traditional measure of hospice use. The lower odds of enrollment for transfusion‐dependent patients suggest that the current hospice model, which largely disallows transfusions, may not be meeting the palliative needs of this population. Cancer 2016;122:1209–15 . © 2016 American Cancer Society . Abstract : A large database analysis demonstrates that the intensity of end‐of‐life care for patients with myelodysplastic syndromes varies but is potentially suboptimal with respect to hospice use. The lower odds of enrollment for transfusion‐dependent patients suggest that the current hospice model, which largely disallows transfusions, may not be meeting the palliative needs of this population.